Aromatic Oligoamide Foldamers with a "Wet Edge" as Inhibitors of the α‐Helix‐Mediated p53–hDM2 Protein–Protein Interaction. Issue 17 (8th May 2013) - Prabhakaran, Panchami; Barnard, Anna; Murphy, Natasha S.; Kilner, Colin A.; Edwards, Thomas A.; Wilson, Andrew J.
Abstract: This paper describes the design, synthesis and structural analysis of a 3‐ O ‐alkylated aromatic oligoamide that incorporates an additional hydrophilic 6‐ O ‐alkyl substituent in the central monomer. This oligomer exhibits low μM inhibitory potency against the p53– h DM2 interaction compared with its unfunctionalised counterpart and significantly improved solubility. Abstract : A 3‐ O ‐alkylated aromatic oligoamide foldamer incorporating an additional and hydrophilic 6‐ O ‐alkyl substituent in the central monomer is shown to have improved solubility, adopt an active binding conformation and disrupt the p53– h DM2 interaction.